Ryzyko bazy w transakcjach terminowych na rynku kapitałowym - Pyka, Irena; Krawczyk, Liwiusz (Basis Risk in Forward Transactions on Capital Market, 2007)
Dynamic development of financial instruments for investors, accompanying the processes of globalization and internationalization of market transactions, is significantly correlated with the increase of the investment risk range. That comprises various individual kinds of risk, including the basis risk constituting the very subject of the paper. It is a specific, investment related risk, since it applies to the options market exclusively. In the paper, the basis risk has been assessed with regard to the example of index futures contracts of GPW S.A. in Warsaw. The basis risk in highly developed markets is lower than in the emerging ones, due to various factors the analysis and assessment of which constitute crucial aspects of the paper purpose accomplishment. The theoretical section is focused on the introduction of basis risk definitions and the notions of strengthening and weakening of the basis, as well as description of the factors determining the risk. The practical section of the paper presents the basis risk in GPW Warsaw in the perspective of futures contracts, with regard to WIG20
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 440-454